Porous ionomer-free layered metal alloy electrocatalytic electrodes

A layered NiFe alloy electrocatalyst fabricated through MS-OAD addresses the inefficiencies of ionomer-degrading catalysts in AEMWE by ensuring stable, high-specific activity without ionomers, enhancing hydrogen production efficiency and reducing costs.

JP2024546367AInactive Publication Date: 2024-12-20CONSEJO SUPERIOR DE INVESTIGACIONES CIENTIFICAS (CSIC) +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024527123
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-11-05
Filing Date
2022-10-21
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing water electrolysis methods for hydrogen production using anion exchange membrane water electrolysis (AEMWE) face challenges with high overpotentials in oxygen evolution reactions (OER) due to the use of ionomers, which can degrade and reduce the effective catalyst surface area, leading to inefficiencies and increased costs.

Method used

The integration of a layered and porous NiFe alloy electrocatalyst, fabricated via magnetron sputtering in oblique angle deposition (MS-OAD), eliminates the need for ionomers by providing a stable, high-specific activity catalyst with controlled porosity and composition, optimized for OER and HER reactions.

Benefits of technology

The ionomer-free electrocatalyst achieves enhanced stability and performance, reducing the amount of active metal required and maintaining electrochemical activity over time, thus lowering costs and improving the efficiency of hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546367000001
    Figure 2024546367000001
  • Figure 2024546367000002
    Figure 2024546367000002
  • Figure 2024546367000003
    Figure 2024546367000003
Patent Text Reader

Abstract

The present invention relates to a new class of electrocatalysts that are incorporated as part of the electrodes, anodes and cathodes, in water electrolysis devices aimed at hydrogen production by electrochemically splitting water into oxygen and hydrogen. The electrocatalysts of the present invention are characterized by a layered and porous structure that provides high performance towards the oxygen evolution reaction in the absence of added ionomers. The object of the present invention is framed in an energy field.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a new kind of electrocatalyst incorporated as part of the electrode in the anode in water electrolysers for hydrogen production by electrochemically splitting water into oxygen and hydrogen. The electrocatalyst is characterized by a layered and porous structure that provides high performance towards the oxygen evolution reaction (OER) in the absence of added ionomer. The object of the present invention is realized in the field of energy. [Background technology]

[0002] Hydrogen is a promising energy vector for clean and sustainable energy use for operations in the domestic, transport, and industrial sectors. Currently, most hydrogen production relies on the reforming of steam methane (or other hydrocarbons). This procedure is responsible for releasing CO2 into the atmosphere in unmanageable amounts. For this reason, alternative hydrogen production processes using environmentally friendly pathways (e.g. electricity from renewable sources) constitute an urgent need without waste emissions. In this context, water electrolysis using intermittent renewable energy sources has emerged as a viable alternative, even on an industrial scale, to such conventional hydrogen production methods known.

[0003] Anion Exchange Membrane Water Electrolysis (AEMWE) is an emerging technology for hydrogen production. It operates at low temperatures (typically up to 80°C) and has several advantages over other more traditional electrolyser types, such as reduced membrane and electrocatalyst costs (e.g., compared to proton exchange membrane water electrolysis, which typically requires a Pt-group metal electrocatalyst), or reduced problems associated with potassium carbonate formation in conventional alkaline electrolysis. [JE Park, SY Kang, S.-H. Oh, JK Kim, MS Lim, C.-Y. Ahn, Y.-H. Cho, Y.-E.Sung, High-performance anion-exchange membrane water electrolysis, Electrochim.Acta.295(2019)99-106]

[0004] Nickel and nickel-transition metal alloy based electrocatalytic electrodes have shown high activity in basic media for both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). The former is the most limiting reaction due to higher overpotential. In this regard, catalysts based on Ni alloy formulations (e.g., Fe / Ni, Mo / Ni, but not limited to these compositions) are known to reduce the OER overpotential, resulting in highly active and low-cost electrocatalysts compared to platinum metal group catalysts. However, improving electrode performance for fabricating AEMWEs involves optimization of the microstructure, porosity, amount, chemistry / composition, and electrochemical surface area of ​​the active phase of the electrocatalyst. [A. Lim, H. Kim, D. Henkensmeier, S. Jong Yoo, J. Young Kim, S. Young Lee, Y.-E. Sung, JH Jang, HS Park, A study on electrode fabrication and operation variables affecting the performance of anion exchange membrane water electrolysis, J.Ind. Eng.Chem.76(2019)410-418]

[0005] Among other requirements, the electrode electrocatalyst must present high electrochemical activity and stability, be inexpensive and have a secure supply. From the operating point, it is also important to achieve precise control over the catalyst microstructure, composition, element distribution, and chemical state. For practical exploitation, in order to reduce the costs associated with the electrocatalyst loading, the electrocatalyst must have high specific activity towards the OER and HER reactions that take place in the electrolyser. These properties and requirements can be optimized by the use of appropriate preparation methods.

[0006] The most common route to fabricate electrodes for water electrolysis involves incorporating a catalyst slurry or ink into a gas diffusion layer (GDL) support. Typically, an ionomer compound is also added to the slurry or ink to facilitate the diffusion of hydroxyl groups to the anode active sites where the oxidation reaction leading to the formation of oxygen takes place. The catalyst itself is mainly prepared as a powder followed by a wetting route such as co-precipitation, hydrothermal, sol-gel, or directly incorporated into the electrode using an electrodeposition method. In these classical approaches, typical steps include the preparation of a precursor solution, a precipitation process, washing, filtering, drying, calcination, and / or milling. An obvious disadvantage of these wetting routes is that they involve solvents that generate undesirable waste and imply a reproducibility handicap when scaling up the electrocatalyst manufacturing procedure.

[0007] Due to the special features and constraints of electrolyzer cells, a good choice of material catalyst is a key requirement, as well as to achieve an optimized integration of the electrocatalyst in the electrodes, the so-called membrane electrode assembly (MEA) and the complete stacked cell. This is not only about finding the best electrocatalyst composition for the anode and cathode OER and HER reactions, or the use of the most appropriate ionomer type and loading, but also the best method to integrate the appropriate electrocatalyst material in the GDL and finally in the cell. Therefore, choosing the most appropriate procedure for the synthesis and integration of the electrocatalyst is a key requirement to optimize the electrocatalyst performance and therefore the cell operation capability.

[0008] Traditional preparation methods for AEMWE catalyst electrodes using slurries or inks often involve the addition of polymeric organic ionomer molecules to increase cell performance. The function of the ionomer is twofold: it acts as a binder to the GDL support, increases the number of ion transport pathways between the electrocatalyst load and the anion exchange membrane, and facilitates the anion diffusion capacity to the reaction sites. This compound affects the gas permeability and, thanks to its charged functional groups, increases the number of water and OH groups at the catalyst surface. - It facilitates the exchange of ions. However, ionomers can also be disadvantageous if, through electrostatic / covalent bonds, their charged groups occupy catalytically active sites and thus increase the overpotentials of the HER and OER. Over time, ionomers can undergo chemical degradation, resulting in a deterioration of the effective catalyst-ionomer interface and therefore also the electrochemically active surface area of ​​the electrode available for reaction. It is therefore clear that the development of new catalyst formulations that avoid the use of said ionomers is necessary to ensure the long-term operation of electrolyzer cells. Summary of the Invention

[0009] The present invention provides that to obtain ionomer-free electrodes, magnetron sputtering in oblique angle deposition geometry (MS-OAD) porous and nanostructured electrodes can be integrated into membrane electrode assemblies and then integrated in a laminate suitable for building AEMWE electrolyzers (devices).

[0010] A first aspect of the invention relates to a layered electrocatalytic electrode having a macroporous gas diffusion layer and current collector material substrate having a thickness of 0.05 mm-1.0 mm, and an electrocatalyst having a uniform thickness of 0.05 μm-5 μm. a layered electrocatalytic electrode, the electrocatalytic layer comprising a first surface and a second surface, the first surface being in contact with a surface of the substrate and the second surface being opposite the first surface in a direction defined by a thickness of the electrocatalytic layer; The substrate is selected from carbon paper, stainless steel, or nickel, the carbon paper, stainless steel, and nickel having a microfiber, sponge, or mesh-like structure; the electrocatalyst layer comprises a NiFe alloy, the Fe in the alloy having a weight average value between 0.5%-30%, the weight of Fe in the NiFe alloy composition of the first surface of the electrocatalyst layer being between 0.5% and 2%, and the weight of Fe in the NiFe alloy composition of the electrocatalyst layer at the second surface being between 12%-30%, The electrocatalyst layer has a surface area of ​​1 to 100 cm for the oxygen evolution reaction (OER) expressed as an area per unit of catalyst loading determined from Nyquist plots of the electrode system by electrical impedance spectroscopy. 2 / mg, The electrocatalytic layer is a mesoporous layer having a porosity between 20%-50% as measured by Kr gas adsorption isotherms and a pore size varying between 2-100 nm as determined by direct quantification on a photographic film of a scanning electron microscope.

[0011] The term "equivalent thickness" as used herein refers to the thickness of NiFe alloy deposited on a flat substrate in the same deposition batch as the electrocatalyst on the GDL.

[0012] The term "electrocatalyst layer" as used herein refers to an alloy layer with controlled composition, porosity and microstructure, which is deposited on a macroporous substrate by magnetron sputtering in an oblique angle geometry. It is an electroactive catalyst layer that induces OER or HER reactions upon application of a polarization potential. In the present invention, the pore size is determined by direct quantification by scanning electron micrographs, and the pore volume is measured by membrane and Kr gas adsorption isotherms. The electrocatalyst layer is placed in contact with the electrolyte under operating conditions through the second surface described above.

[0013] The term "macroporous" as used herein refers to an open pore structure having pore sizes in the range of 5-100 microns as determined by direct observation by scanning electron microscopy. The voids are defined by an array of threads or microfibers, or by a sponge-like or mesh or similar structure, said voids having sizes in the range of 5-100 microns.

[0014] As used herein, the term "macroporous gas diffusion layer and current collector (GDL)" refers to a macroporous material that acts as a support for the electrocatalyst layer. It refers to a woven, microfiber, mesh or sponge-like structure of the substrate in the form of a laminate that can be made of either carbon, nickel, stainless steel or any other material that is stable in the basic medium in which OER occurs.

[0015] The term "electrochemical active surface area (ECSA)" as used herein refers to the equivalent specific area of ​​the electrode material that is accessible to the electrolyte and is used for OER at the anode. It is measured in area per unit of catalyst loading and is determined according to the electrochemical double layer capacitance method from the Nyquist plot of the electrode system by electrical impedance spectroscopy measurements. It is related to the actual surface area of ​​the mesoporous structure of the electrocatalyst layer and defines the effectiveness of a given layer to promote a specific reaction. ECSA can also be determined from any other method based on current-voltage measurements at several voltage scan rates, the so-called capacitance method. In the context of the present invention, it refers to OER.

[0016] The electrocatalyst layers used in the present invention are deposited on rough or macroporous randomly oriented surfaces, as those of typical GDLs formed by aggregation of fine fibers or sponge-like microstructures. They maintain, however, an average mesoporosity, endowing electrocatalyst materials prepared under these conditions with potentially high electrochemical performance. High porosity and high specific ECSA of the electrocatalyst layer, achievable by proper control of the deposition process, are other prerequisites for optimized performance towards OER and HER. The selected GDL macroporous materials exhibit high electronic conductivity, allow outward diffusion of gases (H2 or O2) from the interface between the anion exchange membrane and the electrocatalyst layer of the AEMWE cell, and are highly stable in the basic operating conditions of the electrochemical cell.

[0017] The tailored depth distribution and composition of porosity along the electrocatalyst layer, achievable by proper control of the deposition process, is a further important feature of these electrocatalyst layers.

[0018] Another advantage of the electrode produced by incorporating said electrocatalyst layer onto a GDL substrate as claimed in the present invention is that there is no significant decomposition or peeling of the electrocatalyst layer from the GDL after use, clearly proving the great stability of the electrode, which can further be confirmed by the fact that no traces of Fe and / or Ni were observed after inductively coupled plasma analysis of the alkaline aqueous solution feeding the electrolytic cell after the experiments.

[0019] When applying conventional electrode preparation methods, ionomers are added as binders to the catalyst ink or slurry to favor ion migration transport to the reaction sites. The operation of the electrocatalyst layer of the present invention is not limited by ion migration mechanisms, and considering that no delamination of the active catalyst layer was detected after long-term operation, it is clear that the MS-OAD electrocatalyst does not require any binder to fix the catalyst layer to the GDL support. Thus, the electrocatalyst layer of the electrode of the present invention operates on an ionomer-free base.

[0020] Another advantage of the electrocatalyst in the form of a deposited layer covering the void surfaces of the outermost region of the GDL substrate is that a smaller amount of active metal phase is required for operation. Electrodes prepared as described in this invention show similar electrochemical performance to conventional electrodes prepared by wet chemical routes using active materials (e.g., Ni, NiFe, etc.) that are at least an order of magnitude smaller.

[0021] Another advantage of the proposed alloy electrodes is the control of the depth of the element distribution in the layer structure with different profiles, including homogeneous distribution, bilayer or lamellar distribution or smoothly varying element profile distribution. This allows to tailor the properties of the electrocatalytic layer. For example, to bring into contact with the GDL, the composition supports more quickly the composition in contact with the phase composition that is particularly active towards OER or HER reactions, in the outer zone in contact with the electrolyte. This control also allows the deposition of only a few atomic layers of the most expensive elements in the outer zone to act as an effective electrocatalyst in contact with said electrolyte, thus allowing the electrodes to be used with obvious advantages in terms of the cost of the metals.

[0022] Thus, in a preferred embodiment of the present invention, the GDL macroporous substrate acting as the backing gas diffusion layer and current collector is nickel having the morphology of a mesh-like structure, since this is the most robust against chemical decomposition in basic media.

[0023] In other preferred embodiments, the stoichiometry of the alloy in the electrocatalyst layer has a uniform composition from the first surface to the second surface, or has a linear composition gradient of the weight percent of Fe in the alloy in the direction of the layer thickness from the first surface at the interface with the GDL substrate to the second surface at the outermost external zone in contact with the electrolyte.

[0024] In another preferred embodiment, the stoichiometry of the NiFe alloy is adjusted to an average value between 8%-12% by weight of Fe in the alloy, which ratio ensures a uniform distribution of iron atoms within the nickel atomic lattice and provides maximum current when operated to induce OER.

[0025] In another preferred embodiment, the NiFe alloy composition at the first surface of the electrocatalyst layer is between 0.1%-2% by weight of Fe in the alloy and at the second outer zone is between 10%-20% by weight of Fe in the alloy.

[0026] In other preferred embodiments, the porosity of the electrocatalyst layer has a constant porosity along the entire layer thickness with a value between 20-50% of the total volume of the layer, or the porosity in the electrocatalyst layer varies linearly from the first surface to the second surface, in more preferred embodiments the porosity of the first surface zone is between 20%-30% and the porosity of the second surface zone is between 40%-50%.

[0027] The varying profile of porosity is achieved by varying the gas plasma pressure during MS deposition and / or the deposition angle during MS-OAD.

[0028] In another preferred embodiment, the electrocatalyst at the second surface is Ni(Fe)O x H y The catalyst further comprises a layer of a compound that leads to enhanced surface reactivity, which when combined with the bulk metallic character of the catalyst film, reduces the electrical resistance of the electrode, further contributing to improved performance of the OER electrochemical process.

[0029] As used herein, the term "Ni(Fe)O x H y "Compound" refers to a layer of mixed oxide-hydroxide of Fe and Ni that is considered the active phase for the OER. This layer can be deposited directly by MS-OAD on the outer surface of a NiFe electrocatalytic catalyst, but is most commonly produced from an FeNi alloy by electrochemical cycling of the electrode in a basic medium.

[0030] A second aspect of the invention is a method for obtaining a layered electrocatalytic electrode, characterized in that it comprises the following steps: a) placing a macroporous gas diffusion layer and current collector material substrate selected from carbon paper, stainless steel or nickel, said carbon paper, stainless steel and nickel being in the form of microfiber, sponge or mesh-like structure, as a substrate in a holder of a vacuum chamber of a magnetron sputter deposition apparatus; b) placing a nickel and iron or NiFe alloy target as a target or targeting device in a magnetron sputtering head located in the deposition apparatus of step a), the target having a shape selected from disk, circle, square, cylinder and rectangle, the distance between the target and the substrate being 2 cm-30 cm, and the normal of the substrate surface being at an angle of at least 70° to the normal of the target surface in a racetrack formed on the substrate surface by sputtering in a MS-OAD configuration; c) While the holder rotates at a speed of 1-10 revolutions per minute, -6 Apply a vacuum to the chamber in step (b) until a base pressure of 0.1 mbar or less is achieved, with a flow rate of 20-40 standard cubic centimeters per minute and 5·10 -3 introducing Ar gas at a process pressure of 1000 mbar and applying a pulsed DC power of 50 W-3000 W and a frequency of 80-200 kHz to the target to ignite a magnetron plasma, whereby a layer of NiFe electrocatalytic electrode is deposited; d) Optionally, on the layered electrocatalytic electrode obtained in step (d), Ni(Fe)O is deposited by a technique selected from MS-OAD or electrochemical cycling of the electrode. x H y A process for depositing or producing a layer of a compound.

[0031] Magnetron sputtering deposition technique is a classical physical vapor deposition procedure that is widely utilized in industry for the preparation of compact layers for a wide variety of applications in optics, tribology, hard coatings, etc. The present invention claims is also an optimal choice for the fabrication of porous and nanostructured electrocatalytic layers suitable for their integration into high performance AEMWE cells. Particularly, when this method is utilized in oblique angle deposition configuration (MS-OAD) and specific operating conditions, it provides nanostructured and highly porous electrocatalytic layers, gifted with high electrochemically active surface area, resulting in highly suitable for their incorporation onto GDLs as electrodes in AEMWEs. The method is highly reproducible, scalable to large deposition areas, does not produce residues, and works at room temperature. Careful tuning of deposition geometry and plasma gas pressure during MS-OAD renders mesoporous nanostructured materials with tight control of composition, loading, and microstructure. The resulting nanostructured layer deposited on the GDL facilitates the flow of liquid reactants (basic aqueous solutions) and the evacuation of produced gases (H2, O2) through nano-measurement pathways present in the catalyst decorating the fibrous / macroporous GDL backing. Another advantage of the method of the present invention is the preparation of depth-composition-variable electrocatalyst layers with tailored composition and porosity distribution in depth.

[0032] Thus, in a preferred embodiment of the method of the present invention, the target has a disk shape with a diameter size between 50 mm-100 mm, the pulsed DC power in step (c) is between 50 W-300 W and the frequency is between 80-140 kHz.

[0033] In another preferred embodiment, the nickel / iron target or targets are nickel having a shape selected from disk, circle, square, cylinder and rectangle, more preferably circular with a diameter between 50mm-100mm, a width between 1mm-2mm and a thickness between 0.2-0.3mm, wrapped axially around the disk surface.

[0034] In another preferred embodiment of the process, the target is a NiFe alloy containing between 2.0%-20% Fe by weight.

[0035] To achieve the expected activity of the porous electrocatalyst, it is produced by magnetron sputtering at an oblique angle. Due to the fact that MS-OAD induces an inherently non-uniform deposit on large substrates, the movement of the substrate during deposition is mandatory to achieve a uniform loading on the substrate. Various possibilities exist to achieve a homogeneous deposition.

[0036] In the first MS-OAD configuration option, the experimental setup consists of a rotatable sample holder whose axis is positioned perpendicular to the main direction of the particle flux from one of the magnetron heads, while the GDL backing electrode is attached to the sample holder and rotated continuously during the deposition of the mesoporous electrocatalyst. In these conditions, the ultrafine fiber, sponge, or mesh-like structure of the textured substrate support is decorated with a mesoporous NiFe electrocatalyst layer. On a flat substrate, this geometric configuration and realization procedure renders vertically oriented mesoporous nanocolumnar structures.

[0037] In another preferred embodiment of the process, deposition of the electrocatalyst is performed in even steps with a constant vertical orientation of the GDL substrate with respect to the sputtering target. The sample holder is rotated 180° azimuthally for each deposition step. With this configuration, the substrate surface normal forms an oblique angle with respect to the perpendicular to the target. This second option produces a zigzag microstructure when deposited on a flat substrate. When using a structured GDL support, the result is a nanostructured layer covering the pore surfaces in the shallow regions of the support, and a uniform thickness distribution of the electrocatalyst layer over the entire substrate.

[0038] In another configuration, typically using a rectangular sputtering target, the flexible GDL backing can be mounted on a cylindrical sample holder that rotates continuously around its shaft axis during deposition. This latter configuration is compatible with roll-to-roll procedures and allows for optimization of the deposition of material onto the substrate. In these conditions, the main flow of material from the sputtered target reaches the GDL substrate with an averaged local oblique geometry, thus ensuring high mesoporosity.

[0039] Other possible realizations of the MS-OAD process can also be used to obtain the desired porous microstructure in up to 50% of the layer volume, such as the use of a slit and a linearly movable substrate during deposition, or as a twisting of the substrate when applying a substrate moment, in order to homogenize the thickness of the electrocatalytic layer over the entire substrate. The use of a slit serves to select deposition particles that come from the target within a certain solid angle and reach the substrate obliquely to the surface normal. The inconvenience of this configuration is that only a small portion of the sputtered material coming from the target passes through the slit to the substrate.

[0040] A third aspect of the present invention is a membrane electrode assembly (MEA) characterized in that it comprises two electrodes, at least one of which is an electrode as described above in the present invention and which is an anion exchange membrane.

[0041] As used herein, the term membrane electrode assembly (MEA) refers to an anion exchange membrane sandwiched between an anode and a cathode, which are composed of GLD with corresponding deposited electrocatalysts optimized for OER / HER, respectively. The entire ensemble is embodied and pressed between bipolar metal plates that allow access of the electrolyte, generally an aqueous KOH solution with a given concentration (typically 1.0 M), and releases the produced gases (O2 at the anode, H2 at the cathode).

[0042] A preferred embodiment of the MEA is as follows: One of the electrodes is an electrode as described above in the present invention and is suitable to act as an anode. The second electrode is a porous Ni layer acting as an electrocatalyst. It is deposited following the same MS-OAD procedure from a pure Ni target onto another backing gas diffusion layer and a current collector material suitable to act as the cathode. The assembly between the anode and the cathode is made by an anion exchange membrane, and the electrodes are connected to an external electric circuit that applies the desired voltage difference (generally 1.5-2.5 V) between the anode and the cathode. 1500mA cm depending on electrode size and process efficiency -2 Current densities up to 10 ...

[0043] A fourth aspect of the invention is an anion exchange membrane water electrolysis (AEMWE) electrolyser, characterized in that it comprises a stack of at least two MEA units electrically connected in series in a compact system. In a preferred embodiment, the anion exchange membrane water electrolysis (AEMWE) electrolyser further comprises a stack of five or more MEAs arranged in a compact system such that the electrodes are electrically connected in series. The electrolyte circulates in parallel through the various anode and cathode compartments and the gases are discharged separately through the outlet tubes.

[0044] The term "AEMWE electrolyzer" as used herein refers to a compact stacked system of several MEAs as described above, with appropriate shielding gaskets and plates, gas inlets and outlets, etc., where the aqueous electrolyte is adjusted to basic conditions, typically pH=10 or higher.

[0045] A fifth aspect of the present invention is a method for producing hydrogen, comprising the following steps: (i) Supplying the AEMWE electrolyser as described above in the present invention with 0.1M-4M aqueous KOH solution at a temperature between 40°C-85°C. (ii) A polarization voltage between 1.8V-2.2V is applied to each of the MEA unit cells and they are electrically connected in series within the stack.

[0046] In a preferred embodiment, the temperature of step (i) is 60° C.-80° C. An advantage of the AEMWE electrolyser constructed in this way is that it can be operated without adding ionomer to the electrocatalyst, thus avoiding operational problems related to electrodes and electrode degradation or fouling, and facilitating long operating times. Another advantage is the significant reduction in the amount of active phase in the electrocatalyst, and the resulting reduction in the associated costs.

[0047] A sixth aspect of the present invention is the use of a layered electrocatalytic electrode as described above in the present invention as an anode in an AEMWE electrolyser.

[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs. Methods and materials similar or equivalent to those described herein can be used in the practice of this invention. Throughout the specification and claims, the word "comprises" and variations thereof are not intended to exclude other technologies. Features, additives, components, or steps, further objects, advantages, and features of the invention will become apparent to those skilled in the art upon examination of the description or can be learned by practice of the invention. The following examples, figures, and sequence listings are provided by way of illustration and are not intended to limit the invention. [Brief description of the drawings]

[0049] [Figure 1] FIG. 1 is a schematic diagram of the geometry of the MS-OAD process used to prepare the electrocatalysts in Examples 1-5 and Comparative Example 6. [Diagram 2] FIG. 2 is a diffractogram of the prepared NiFe bimetallic electrocatalyst used as the anode in Experimental Examples 1-5 and Comparative Example 6. [Diagram 3] FIG. 3 is an enlarged view of the diffractogram around the Ni(220) diffraction peak of the prepared NiFe bimetallic electrocatalyst used as the anode in Experimental Examples 1-5 and Comparative Example 6. [Figure 4] FIG. 4 shows cyclic voltammetry experiments carried out on the electrocatalysts prepared in Experimental Examples 1-5 and Comparative Example 6 at room temperature, 1.0 M KOH electrolyte and a scan rate of 20 mV / s. [Diagram 5] FIG. 5 shows SEM images in normal view of the EE-10% Fe-Ni (EE, electrocatalytic electrode) electrocatalyst prepared and after its use in a three-electrode glass cell. [Figure 6] Temperature. Linear sweep voltammetry characteristics of the electrocatalysts prepared in Example 2 and integrated in a single MEA electrolysis cell according to Example 4 at operating temperatures of 40° C. and 60° C. [Figure 7] Ionomer. Linear sweep voltammetry characteristics of electrocatalysts prepared in Example 2 integrated in a single MEA electrolysis cell with and without ionomer at an operating temperature of 40° C. [Figure 8] 8 shows the stability: first and second hundred cycle linear sweep voltammetry characteristics of the electrochemically active material prepared in Example 2 and integrated into a single MEA electrolysis cell according to Example 4 at an operating temperature of 40° C. [Figure 9] Figure 9 shows the stability of electrocatalysts prepared in Example 2, galvanostatic chronopotentiometric measurements taken at 400 mA / cm2 and 40°C for 2 days and integrated in a single MEA electrolysis cell at an operating temperature of 40°C. Experimental Example

[0050] <Experimental Example 1> An electrocatalytic electrode EE-(5%Fe)Ni was prepared for an AEMWE electrolyzer.

[0051] The NiFe bimetallic electrocatalytic electrode of the present invention was prepared at room temperature (25°C) by MS-OAD with the geometry as described in Figure 1. One axially wound iron strip (GoodFellow Cambridge Ltd., 99.5 at%, 1.5 mm wide, 0.25 mm thick) on a circular nickel sputtering target (GoodFellow Cambridge Ltd., 99.9 at% 50 mm diameter) was used as the source of bimetallic alloy. The sputtering target was operated using a 150 W pulsed DC power supply (AE Pinnacle+) and a frequency of 120 kHz. Carbon paper GDL firing electrode (TGP-H-90, Fuel Cell Earth) was used as the substrate.

[0052] A similar electrocatalyst layer can be prepared by replacing the Ni target with an Fe strip by an FeNi alloy target having the desired composition.

[0053] The carbon paper substrate was placed on a circular rotatable sample holder with a diameter of 10 cm. This holder was placed at an angle of ~78° to the surface of the sputtering target and rotated continuously at 5 revolutions per minute to homogenize the thickness and microstructure of the deposited film. This configuration is also compatible with deposition from two targets placed at a similar radial position relative to the rotating disk. Argon was used as the plasma gas. A flow of 30 SCCM (SCCM / standard cubic centimeters per minute) was administered into the preparation chamber, and 5·10 -3 The base pressure in the system was 2·10 -6 The pressure was 100 mbar. A deposition time of 100 min was required to achieve the desired amount of electrocatalyst. The deposition rate was about 5 nm of uniform thickness of deposited material per minute.

[0054] Carbon paper (TGP-H-90, Fuel Cell Earth) was used as the support for the electrocatalyst. In addition, polished silicon wafers were also used as substrates for cross-sectional microscopy analysis of the different nickel-based thin films. We define the equivalent thickness as the physical thickness determined by cross-sectional SEM analysis for thin films simultaneously deposited on a flat silicon wafer substrate. In these conditions, the iron content in the nanostructured bimetallic NiFe alloy deposits was about 5 wt.%.

[0055] <Experimental Example 2> An electrocatalytic electrode EE-(10%Fe)Ni was prepared for an AEMWE electrolyzer.

[0056] Electrocatalytic electrodes for AEMWE electrolyzers were prepared in a similar manner to Example 1, except that the number of iron strips wrapped around the Ni sputtering target was divided into two equal parts. Under these conditions, the iron content in the nanostructured bimetallic NiFe alloy deposit was about 10 wt.%.

[0057] A similar electrocatalyst layer can be prepared by replacing the Ni target with an Fe strip by an FeNi alloy target having the desired composition.

[0058] <Experimental Example 3> An electrocatalytic electrode EE-(15%Fe)Ni for an AEMWE electrolyzer was prepared.

[0059] Electrocatalytic electrodes for AEMWE electrolyzers were prepared in a similar manner to Example 1, except that the number of iron strips wrapped around the Ni sputtering target was divided into three equal parts. Under these conditions, the iron content in the nanostructured bimetallic NiFe alloy deposit was about 15 wt.%.

[0060] A similar electrocatalyst layer can be prepared by replacing the Ni target with an Fe strip by an FeNi alloy target having the desired composition.

[0061] <Experimental Example 4> An electrocatalytic electrode EE-(20%Fe)Ni for an AEMWE electrolyzer was prepared.

[0062] Electrocatalytic electrodes for AEMWE electrolyzers were prepared in a similar manner to Example 1, except that the number of iron strips wrapped around the Ni sputtering target was divided into four equal parts. Under these conditions, the iron content in the nanostructured bimetallic NiFe alloy deposit was about 20 wt.%.

[0063] A similar electrocatalyst layer can be prepared by replacing the Ni target with the Fe strips by an FeNi alloy target having the desired composition.

[0064] <Experimental Example 5> An electrocatalytic electrode EE-(30%Fe)Ni for an AEMWE electrolyzer was prepared.

[0065] Electrocatalytic electrodes for AEMWE electrolyzers were prepared in a similar manner to Example 1, except that the number of iron strips wrapped around the Ni sputtering target was divided into 6 equal parts. Under these conditions, the iron content in the nanostructured bimetallic NiFe alloy was about 30 wt.%.

[0066] A similar electrocatalyst layer can be prepared by replacing the Ni target with an Fe strip by an FeNi alloy target having the desired composition.

[0067] <Experimental Example 6> An electrocatalytic electrode EE-Ni for an AEMWE electrolyzer was prepared.

[0068] A reference nanostructured electrocatalytic electrode for an AEMWE electrolyser was prepared similarly to Example 1, except that there was no iron strip wrapped around the Ni sputtering target.

[0069] <Experimental Example 7> Comparative X-ray diffraction analysis

[0070] The electrocatalytic electrodes prepared in Experimental Examples 1-5 and Comparative Example 6 were analyzed by X-ray diffraction (XRD). Figure 2 shows the diffractograms of the prepared NiFe bimetallic metal anodes. They serve as fingerprint analysis of the different prepared electrocatalysts. They show that the catalysts are mostly polycrystalline (weak diffraction peaks are detected), and thus deposition occurs. The process is at room temperature, and the iron atoms are incorporated into the nickel atomic network.

[0071] The diffractogram in Figure 2 shows a characteristic strong diffraction peak at 54.6° due to the carbon paper used as the substrate. In addition, two smaller diffraction peaks at about 44.5° and 51.9° are due to metallic nickel or Ni-containing alloys.

[0072] A close-up of the 44.5° peaks due to the Ni(220) reflection in the metal-based Ni network is shown in Figure 3, where it is clear that their intensity decreases. Their width increases and their position shifts as the iron content in the sample increases. These effects are due to the random incorporation of iron atoms within the face-centreed cubic (fcc) structure of Ni, forming a kind of alloy. The lack of diffraction reflections due to metallic Fe confirms the incorporation of Fe into the Ni structure. Overall, this XRD analysis shows that the bimetallic electrode consists of a metal alloy with a small crystallite grain size.

[0073] <Experimental Example 8> Experimental example for evaluation of electrochemical properties of electrocatalytic electrodes in a half-cell configuration

[0074] The electrocatalytic electrodes prepared in Experimental Examples 1-5 and Comparative Example 6 were evaluated for performance towards OER in a three-electrode glass cell (half-cell configuration).

[0075] The cell is connected to a working anode (1.0 cm 2 The device incorporates a 1000-millimeter square meter (geometric area of ​​100 nm), an Ag / AgCl reference electrode (KCI, 3M, Metrohm®) and a platinum foil (Metrohm®) counter electrode.

[0076] The electrochemical characterization consisted of cyclic voltammetry (CV) measurements. They were performed using an Autolab PGSTAT 30-ECOCHEMIE potentiostat / galvanostat. All measurements were performed at room temperature and in 1.0 M KOH aqueous electrolyte. Before testing the electrodes, a stream of nitrogen gas was bubbled through them for at least 20 min and then maintained during the experiment. The voltage range in the CV measurements was 0.00 to +750 mV vs. Ag / AgCl.CV and the scan rate was 20 mV / s.

[0077] 4 shows cyclic voltammetry experiments carried out in a three electrode glass cell at room temperature for the electrodes prepared in Experimental Examples 1-5 and Comparative Example 6. The electrolyte was 1.0 M KOH and the scan rate was 20 mV / s.

[0078] As shown in Figure 4, the incorporation of iron has a positive effect on the OER activity, resulting in a significant increase in the current density values ​​(magnitude proportional to O2 formation at the anode) with respect to those obtained for Ni. The electrocatalyst prepared in Comparative Example 6 shows that the improvement in electrocatalytic activity due to the incorporation of iron is greater than 10 mA / cm2. 2 The overpotential value required to reach was the lowest for the EE-(10%Fe)Ni anode (i.e., 307 mV).

[0079] This enhancement is due to the Ni in Ni(OH)2 and NiOOH. +2 Fe for each site +3 This is associated with the substitution of Ni-0, leading to a new Ni-0 local environment with superior activity for OER. Figure 4 shows that the addition of increasing amounts of Fe to the Ni catalyst favors OER activity up to 10 wt% of Fe incorporated into the nickel structure in the alloy. Then, for iron incorporation percentages higher than 10 wt%, a plateau in the response toward OER is achieved.

[0080] <Experimental Example 9> Experimental example regarding SEM analysis of the prepared and used electrocatalyst

[0081] The electrocatalytic electrodes prepared in Example 2 were analyzed by scanning electron microscopy after operation in a half-cell configuration.

[0082] Figure 5 shows that SEM analysis of the used electrode revealed a similar morphology and microstructure to the as-prepared electrode. This observation discards the delamination of the catalyst from the backing support in the used electrode and confirms the stability of the bimetallic electrode.

[0083] Example 10 This example is directed to the fabrication of a complete electrolysis cell with a single MEA.

[0084] EE-(10%Fe)Ni electrode (catalyst loading 0.35mg / cm) as described in Example 2 2 , uniform thickness 540 nm) as the anode, and an EE-Ni electrode (loading 0.38 mg cm ) was used as described in Comparative Example 1. -2 A ZnO thin film with a uniform thickness of 540 nm was used as the cathode.

[0085] The catalyst film is 6.25 cm 2 The carbon paper was deposited with a geometric area of ​​100 nm.

[0086] The electrodes were separated by an anion exchange membrane (Fumapem® FAA-3-50 supplied by Fuel Cell Store). The geometric area of ​​the electrodes in the MEA was 5 cm 2 and the catalyst loading was determined by weighing before and after MS-OAD deposition.

[0087] Prior to use, the Fumapem® FAA-3-50 anion exchange membrane was immersed in 1.0 M KOH solution at room temperature for 24 hours to activate it, i.e., to remove Br in the pure membrane. - Functional group OH - The group was substituted.

[0088] Nickel bipolar plates with flow channels were used as current collectors and distributors for reactants and products. The anode and cathode reservoirs were supplied with KOH aqueous electrolyte solution with a flow rate of 2 ml / min. A peristaltic pump (Pump Drive 5001, Heidolph) was used to impulse electrolyte solution from two independent 1.0 liter buffer compartments into the electrode reservoirs, recirculating the flow. Teflon gaskets were used to prevent gas leakage and avoid short circuits. The bolt torque applied to seal the cell was selected to optimize the electrochemical performance of the cell.

[0089] <Experimental Example 11> Experimental Example on Electrochemical Characterization of MEA: Performance vs. Operating Temperature

[0090] The electrocatalysts prepared in Example 2 were evaluated for their electrochemical properties towards hydrogen production in a complete electrolysis cell formed by a single MEA, as described in Example 10.

[0091] Electrochemical measurements of the complete AEMWE cell were performed using an Autolab potentiostat / galvanostat. Experiments were performed with linear sweep voltammetry (LSV) varying the potential from 1.0-2.2 V at a scan rate of 5 mV / s, with process temperatures at 40 °C and 60 °C.

[0092] FIG. 6 shows the linear sweep voltammetry characteristics of the cell at operating temperatures of 40° C. and 60° C.

[0093] <Experimental Example 12> Experimental example on electrochemical characterization of MEA: Performance with respect to incorporation of ionomer in electrode

[0094] The electrocatalyst prepared in Example 2 was evaluated for its electrochemical properties for hydrogen production in a membrane electrode assembly with the same conditions in Example 10, except that ionomer was added on top of the electrocatalyst before the MEA assembly.

[0095] The current density versus polarization voltage characteristics of the cell are shown in Figure 7. A significant decrease in performance was attributed to the addition of ionomer to the cell.

[0096] <Experimental Example 13> This is an experimental example regarding the stability of an electrode catalyst incorporated in an MEA.

[0097] The electrocatalyst prepared in Example 2 and incorporated into the MEA described in Example 10 was evaluated for stability under operating conditions.

[0098] Aging experiments were performed by cyclic voltammetry measurements (200 volt cycles, performed at 40° C. and a scan rate of 50 mV / s). Figure 8 shows that no significant variation of the initial characteristics is observed, thus proving the stability of the cells.

[0099] Constant current chronopotentiometric experiments measured the voltage output of the cell and measured the current at 400mA / cm 2 The test consisted of measuring the density current at 40° C. for 2 days. Figure 9 shows that only a weak increase in voltage occurs over time (approximately 5 mV / h), thus proving the stability of the cell.

Claims

1. a macroporous gas diffusion layer and current collector material substrate having a thickness of 0.05-1.0 mm; an electrocatalytic layer having a uniform thickness of 0.05 μm-5 μm; a layered electrocatalytic electrode, the electrocatalytic layer including a first surface and a second surface, the first surface being in contact with a surface of the substrate and the second surface being opposite the first surface in a direction defined by a thickness of the electrocatalytic layer; The substrate is selected from carbon paper, stainless steel, or nickel, the carbon paper, stainless steel, and nickel having a microfiber, sponge, or mesh-like structure; the electrocatalyst layer comprises a NiFe alloy, the Fe in the alloy having a weight average value of 0.5%-30%, the weight of Fe in the NiFe alloy composition of the first surface of the electrocatalyst layer being between 0.5%-2% and the weight of Fe in the NiFe alloy composition of the electrocatalyst layer at the second surface being between 12%-30%; The electrocatalyst layer has a surface area of ​​1 to 100 cm for oxygen evolution reaction expressed as an area per unit of catalyst loading determined from a Nyquist plot of the electrode system by electrical impedance spectroscopy. 2 / mg, 1. A layered electrocatalytic electrode, characterized in that the electrocatalytic layer is a mesoporous layer having a total porosity between 20%-50% as measured by Kr gas adsorption isotherm and pore sizes varying between 2-100 nm as determined by direct quantification on photographic films of a scanning electron microscope.

2. 2. The layered electrocatalytic electrode of claim 1, wherein the substrate gas diffusion layer and the macroporous substrate as the current collector are nickel in the form of a mesh-like structure.

3. 3. The layered electrocatalyst electrode of claim 1 or 2, wherein the stoichiometry of the alloy in the electrocatalyst layer has a uniform composition from the first surface to the second surface, or the stoichiometry of the alloy in the electrocatalyst layer has a linear composition gradient of weight percent Fe in the alloy in the direction of the layer thickness from the first surface in contact with the GDL substrate to the second surface in the outermost region.

4. A layered electrocatalytic electrode according to any one of claims 1 to 3, wherein the NiFe alloy has an average value of 8% to 12% by weight of Fe in the alloy.

5. 5. A layered electrocatalytic electrode according to any one of claims 1 to 4, wherein the NiFe alloy composition of the first surface of the electrocatalytic layer is between 0.1%-2% by weight of Fe in the alloy and in the second outer region the weight of Fe in the alloy is between 10%-20%.

6. 6. A layered electrocatalytic electrode according to any one of claims 1 to 5, wherein the porosity of the electrocatalytic layer has a constant porosity along the entire layer thickness and has a value of 20-50% of the total volume of the layer, or the porosity in the electrocatalytic layer varies linearly from the first surface to the second surface.

7. The second surface of the electrocatalyst layer is made of Ni(Fe)O x H y 7. A layered electrocatalytic electrode according to any one of claims 1 to 6, further comprising a layer of a compound.

8. A method for obtaining a layered electrocatalytic electrode according to any one of the preceding claims, characterized in that it comprises the following steps: a) placing a macroporous gas diffusion layer and current collector material substrate selected from carbon paper, stainless steel or nickel, said carbon paper, stainless steel and nickel being in the form of microfiber, sponge, mesh-like structure, as a substrate in a holder of a vacuum chamber of a magnetron sputter deposition apparatus; b) placing a nickel and iron or NiFe alloy target as a target or targeting element in a magnetron sputtering head located in the deposition apparatus of step a), the target having a shape selected from disk, circle, square, cylinder and rectangle, the distance between the target and the substrate being 2 cm-30 cm, and the normal of the substrate surface being at an angle of at least 70° to the normal of the target surface in a racetrack formed on the substrate surface by sputtering in an MS-OAD configuration; c) While the holder rotates at a rotation speed of 1-10 revolutions per minute, -6 A vacuum is applied in the chamber of step (b) until a base pressure of 0.1 MPa or less is achieved, a flow rate of 20-40 standard cubic centimeters per minute and a pressure of 5-10 -3 introducing Ar gas at a process pressure of 1000 MPa and applying a pulsed DC power of 50 W-3000 W and a frequency of 80-200 kHz to the target to ignite a magnetron plasma, whereby a layer of NiFe electrocatalytic electrode is deposited; And, although optional, d) depositing Ni(Fe)O on the layered electrocatalytic electrode obtained in step (d) by a technique selected from MS-OAD or electrochemical cycling of the electrode; x H y A process for depositing or producing a layer of a compound.

9. 9. The method of claim 8, wherein the nickel / iron target or targets is nickel having a shape selected from a disk, a square, a cylinder and a rectangle, more preferably having a circular shape with a diameter of 50-100 mm, a width of 1 mm-2 mm, a thickness of 0.2-0.3 mm and wrapped axially around a disk surface.

10. A metallic electrode assembly comprising two electrodes, at least one of said electrodes being a layered electrocatalytic electrode according to any one of claims 1 to 7.

11. 11. The metal electrode assembly of claim 10, one of the electrodes is a layered electrocatalytic electrode adapted to act as an anode; The second electrode acts as an electrocatalyst and is a porous Ni layer deposited in another backing gas following the same MS-OAD procedure, with a diffusion layer and current collector material suitable for acting as a cathode; The assembly between the anode and the cathode is made by an anion exchange membrane, and the electrodes are connected to an external electric circuit that applies the desired voltage difference between the anode and the cathode, typically 1.5-2.5V.

12. 12. An AEMWE electrolyser, characterised in that it comprises a stack of at least two MEA units according to any one of claims 10 or 11 electrically connected in series in a compact system.

13. 13. The AEMWE electrolyser according to claim 12, further comprising a stack of five or more MEAs arranged in a compact system such that the electrodes are connected in series, the electrolyte circulates in parallel through the various anode and cathode compartments and the gases are discharged separately through the inlet and outlet tubes.

14. A method for producing hydrogen, comprising the steps of: (i) The anion exchange membrane water electrolyzer according to claim 10 or 11 is treated with a KOH solution between 0.1 M and 4 M at a temperature between 40° C. and 85° C., preferably at a temperature between 60° C. and 80° C. in step i). o filling the space between the spaces C with material; (ii) applying a polarization voltage of 1.8V-2.2V to each of the metal electrode unit cells and electrically connecting them in series within the stack.

15. 8. Use of a layered electrocatalytic electrode according to any one of claims 1 to 7 as an anode in a water electrolysis device.